A new leafhopper genus Bhatiahamus (Hemiptera: Cicadellidae: Deltocephalinae) from China with description of a new species and a new combination - Lu, Lin; Zhang, Yalin (Zootaxa, 2014)
A new leafhopper genus, Bhatiahamus gen. nov., is established for B. flabellatus (Shang & Shen) n. comb. (Bhatia) (type species) and B. sinuatus sp. nov., both from China. A key to distinguish the two species is provided.